2007
DOI: 10.4049/jimmunol.178.8.5383
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Complexes (IC) and IC-Induced Levels of GM-CSF Are Increased in Sudanese Patients with Acute Visceral Leishmania donovani Infection Undergoing Sodium Stibogluconate Treatment: Implications for Disease Pathogenesis

Abstract: Infection with Leishmania donovani is associated with IL-10 as well as with GM-CSF. Immune complexes (IC) exert important functions by stimulation of monocytes/macrophage-mediated production of pro- and anti-inflammatory cytokines in rheumatic diseases. In this investigation, we have explored IC-induced cytokine production during Leishmania infection. Sera from 43 patients with visceral leishmaniasis (VL), 17 patients with post-kala-azar dermal leishmaniasis, and 20 healthy Sudanese controls were precipitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
2
28
0
1
Order By: Relevance
“…Experimental models of VL indicate that B cells and antibodies contribute to parasite persistence because B-cell-deficient mice have enhanced resistance to L. donovani infection [79]. Circulating antibodies and Fc receptors have a crucial role in the pathogenesis of non-healing lesions due to L. mexicana complex parasites in mice [80,81] and immune complexes precipitated from VL serum induce higher levels of IL-10 and other proinflammatory cytokines in PBMCs compared with control sera [70]. Moreover, immune complex formation contributes to high level IL-10 production by both human and mouse macrophages [78,82].…”
Section: Regulatory T Cells In Vlmentioning
confidence: 98%
See 1 more Smart Citation
“…Experimental models of VL indicate that B cells and antibodies contribute to parasite persistence because B-cell-deficient mice have enhanced resistance to L. donovani infection [79]. Circulating antibodies and Fc receptors have a crucial role in the pathogenesis of non-healing lesions due to L. mexicana complex parasites in mice [80,81] and immune complexes precipitated from VL serum induce higher levels of IL-10 and other proinflammatory cytokines in PBMCs compared with control sera [70]. Moreover, immune complex formation contributes to high level IL-10 production by both human and mouse macrophages [78,82].…”
Section: Regulatory T Cells In Vlmentioning
confidence: 98%
“…Apart from being useful in diagnosis of disease, the antibody response in VL patients does not appear to be of benefit to the patient. There are several clinical case reports of autoantibody production and immune complex formation in VL patients [70][71][72][73]. Signs of autoreactivity, such as vasculitis [74,75] and decreased renal function [76,77], have been observed.…”
Section: Regulatory T Cells In Vlmentioning
confidence: 99%
“…Analysis performed with antiserum to IgG1 subclass showed only one part of serum IgG1 molecules precipitated by PEG. However, serum proteins are not denatured during PEG precipitations, and this method is still used for the isolation and in vitro studies of biological effects of immune complexes (Elshafie et al, 2007;Mathsson et al, 2007). In older calves (two, three and four-months old), as well as in adult cattle, all molecular forms of serum IgG1 were precipitated by PEG.…”
Section: Resultsmentioning
confidence: 99%
“…(1989) demonstrated that soluble ICs can lead to sustained superoxide production [27], [52]. Soluble ICs isolated from Leishmania donovani -infected patients have been shown to modulate macrophage responses in vitro with a significant increase in GM-CSF production [53]. Not surprisingly, the context of the soluble IC/macrophage interaction is important, as some studies using ICs have demonstrated IL-10-dependent immunoregulation [54], [55].…”
Section: Discussionmentioning
confidence: 99%